The Role and Application of Comprehensive Budget Management in Hospital Cost Control - Han, Wang (Journal of Global Economy, Business and Finance, 2025)
With the continuous deepening of China’s medical reform policy, it has had a considerable impact and influence on the application of public hospitals. Comprehensive budget management is an important component of hospital internal management and an effective measure to improve the overall operation and management level of hospitals. This article analyzes the role and application of comprehensive budget management in hospital cost control under the new medical reform situation. It conducts an analysis of the importance of comprehensive budget, the application status of comprehensive budget, discusses the existing problems, and proposes targeted and effective solutions, thereby providing useful references for the implementation of comprehensive budget management in public hospitals.